COVID-19 virus behavior simulation model: Case of study Bogotá, Colombia - Sandoval Muelas, Diomedes Arnoldo; Pedroza Martínez, David Ricardo; Casas Pérez, Diego Fernando; Pineda Rincón, Ivanov Alexander; Villanueva Rojas, Estefania; Beltrán Vargas, Julio Eduardo (TECCIENCIA, 2021)
Objetive The purpose of this article is to present a prediction on the epidemiological behavior of the COVID-19 virus for the city of Bogotá, Colombia and determine the possible incidence of the different restriction measures. Material and Methods: a dynamic model based on state information was built for all the analysis variables in the framework of a SEIR model. Results and Conclusions: it was determined that the incidence of effective isolation measures significantly affects the behavior of the disease. Results are presented for two different scenarios, with their respective sensitivity analysis using the Monte Carlo method. It is concluded that it is necessary to increase testing and reduce the time needed to get the results. It is also crucial to generate and deploy social policies that make the fulfilment of an effective quarantine possible. Finally, the restrictions of the model for decision-making in terms of public policy are shown.